The Expanding Digital Media Landscape of Qualitative and Decolonizing Research: Examining Collaborative Podcasting as a Research Method - Lindsay Day; Ashlee Cunsolo; Heather Castleden; Debbie Martin; Catherine Hart; Tim Anaviapik-Soucie; George Russell; Clifford Paul; Cate Dewey; Sherilee L. Harper (MediaTropes, 2017)
Technology of the twenty-first century has transformed our ability to create, modify, store, and share digital media and, in so doing, has presented new possibilities for how social science research can be conducted and mobilized. This paper introduces the use of collaborative podcasting as a research method of critical inquiry and knowledge mobilization. Using a case study, we describe the methodological process that our transdisciplinary team engaged in to create the Water Dialogues podcast, a collaborative initiative stemming from a larger research project examining approaches to implementing Indigenous and Western knowledge in water research and management. We situate collaborative podcasting within an expanding field of collaborative and participatory media practice in social research, and consider how the method may align with and support research within a decolonizing agenda.